Transformasi Sosial Budaya di Pasar Tradisional di Tengah Modernisasi : studi kasus pasar baru kota probolinggo - Verto Septiandika; Putri Aalia; Vivi Yunika Sari; Ummi Kulsum; Ahmad Maman; Muhammad Hasan6 (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
Traditional markets serve not only as centers for economic transactions but also as spaces for social interaction and the preservation of community culture. However, the development of modernization and the emergence of modern and digital markets have brought significant changes to the function and existence of traditional markets. This study aims to analyze the socio-cultural transformations occurring in traditional markets amidst the currents of modernization, with a focus on changing interaction patterns, cultural values, and the role of markets in community social life. The research method used is a descriptive qualitative approach through observation, interviews, and literature review. The results indicate that traditional markets have undergone changes in communication patterns, buying and selling habits, and a shift in shared values ​​toward more practical interaction patterns. Nevertheless, traditional markets continue to play a vital role as irreplaceable socio-cultural spaces, particularly in preserving local traditions and strengthening community social solidarity.